Penegakan Hukum Terhadap Penghindaran Pajak Di Indonesia: Tinjauan Atas Efektivitas Undang-Undang Ketentuan Umum dan Tata Cara Perpajakan (UU KUP) - Nayla Marwa Nur faizah; Ratih Damayanti (Mahalini: Journal of Business Law, 2025)
Tax avoidance is one of the main challenges in Indonesia's tax system, especially since this practice is formally legal but contrary to the spirit of fiscal justice. This study analyzes the legal arrangements regarding tax avoidance in Law Number 6 Year 1983 on General Provisions and Tax Procedures (KUP Law), which has been updated through Law Number 7 Year 2021 on Harmonization of Tax Regulations (HPP Law), as well as its implementing regulations. Although not explicitly categorized as a criminal offense, the authority of the Directorate General of Taxes (DGT) in correcting transactions based on the principle of substance over form and the use of schemes such as transfer pricing, special audit, and advanced pricing agreement are concrete steps in tackling tax avoidance. This study also highlights the obstacles faced by tax law enforcement officers, including: (1) substantive legal lacunae related to the definition and sanctions on tax avoidance; (2) limited access to cross-jurisdictional information despite AEOI; (3) lack of human resource capacity and technology in analyzing complex avoidance schemes; and (4) weak coordination between law enforcement agencies. This study recommends strengthening the General Anti-Avoidance Rule (GAAR) and developing the Specific Anti-Avoidance Rule (SAAR), as well as increasing the competence and analytical tools of tax officials.